2004
DOI: 10.1114/b:abme.0000036646.17362.c4
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional, Quantitative Analysis of Desmin and Smooth Muscle Alpha Actin Expression During Angiogenesis

Abstract: Angiogenic therapies have been designed for many pathological conditions, but when used as a single therapy, the clinical results have fallen short of expectations. In addition, strategies for vascularizing engineered tissues have been unsuccessful in promoting the formation of an extensive, stable vasculature. Recent evidence suggests that mural cells play a critical role in the success of these approaches, but our current understanding of the function of mural cells in the microvasculature is incomplete. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Adding a low concentration of growth factor such as VEGF or fibroblast growth factor-1 leads to a persistent and normal vascular response [77][78][79]. Co-culturing endothelial cells with mural cells (pericytes, smooth muscle cells) significantly accelerates the prevascularization process in fibrin gels (16 vessels per unit area for co-culture compared to nine to 12 vessels for individual culture), and it can also stabilize the capillary once formed [76,80]. Moreover, an in vitro prevascularized fibrin gel using EPC-ECs and fibroblasts implanted subcutaneously into an immune-compromised mouse will anastomose with the host within 27 h after implantation with an average of 150 vessels/mm 2 [16].…”
Section: Fibrinmentioning
confidence: 97%
“…Adding a low concentration of growth factor such as VEGF or fibroblast growth factor-1 leads to a persistent and normal vascular response [77][78][79]. Co-culturing endothelial cells with mural cells (pericytes, smooth muscle cells) significantly accelerates the prevascularization process in fibrin gels (16 vessels per unit area for co-culture compared to nine to 12 vessels for individual culture), and it can also stabilize the capillary once formed [76,80]. Moreover, an in vitro prevascularized fibrin gel using EPC-ECs and fibroblasts implanted subcutaneously into an immune-compromised mouse will anastomose with the host within 27 h after implantation with an average of 150 vessels/mm 2 [16].…”
Section: Fibrinmentioning
confidence: 97%
“…For applications that investigated small tissue areas, such as in the studies reported here, histological evaluation is the most common method of assessment of angiogenesis. In the current studies, angiogenesis was monitored via immune-staining against sma, which is present on the surface of mature blood vessels (vessels with connected venous and arterial branches) [45][46][47]. Since the delivery system presented here was developed for implantable biosensors, the area nearest to the composite (200 μm from the composite surface) was utilized in counting blood capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Vessel stability is likely a function of both the relative levels and composition of BM assembled combined with additional EC interactions with support cells, or pericytes. 29,35 Proteins in the BM may also play an active role in initiating neovascularization. Type IV collagen in the BM contains a matricryptic angiogenic site that is exposed after proteolysis.…”
Section: Initiation Of Neovascularizationmentioning
confidence: 99%